Seawater intrusion effects on nitrogen cycling in the regulated Nakdong River Estuary, South Korea - Huang, Yan; Song, Bongkeun; Zhang, Qinglong; Park, Yunjung; Wilson, Stephanie J.; Tobias, Craig R.; An, Soonmo (Frontiers in Marine Science, 2024)
Research on the impact of seawater intrusion on nitrogen (N) cycling in coastal estuarine ecosystems is crucial; however, there is still a lack of relevant research conducted under in-situ field conditions. The effects of elevated salinity on N cycling processes and microbiomes were examined in situ seawater intrusion experiments conducted from 2019 to 2021 in the Nakdong River Estuary (South Korea), where an estuarine dam regulates tidal hydrodynamics. After the opening of the Nakdong Estuary Dam (seawater intrusion event), the density difference between seawater and freshwater resulted in varying degrees of seawater trapping at topographically deep stations. Bottom-water oxygen conditions had been altered in normoxia, hypoxia, and weak hypoxia due to the different degrees of seawater trapping in 2019, 2020, and 2021, respectively. Denitrification mostly dominated the nitrate (NO3-) reduction process, except in 2020 after seawater intrusion. However, denitrification rates decreased because of reduced coupled nitrification after seawater intrusion due to the dissolved oxygen limitation in 2020. Dissimilatory nitrate reduction to ammonium (DNRA) rates immediately increased after seawater intrusion in 2020, replacing denitrification as the dominant pathway in the NO3- reduction process. The enhanced DNRA rate was mainly due to the abundant organic matter associated with seawater invasion and more reducing environment (maybe sulfide enhancement effects) under high seawater-trapping conditions. Denitrification increased in 2021 after seawater intrusion during weak hypoxia; however, DNRA did not change. Small seawater intrusion in 2019 caused no seawater trapping and overall normoxic condition, though a slight shift from denitrification to DNRA was observed. Metagenomic analysis revealed a decrease in overall denitrification-associated genes in response to seawater intrusion in 2019 and 2020, while DNRA-associated gene abundance increased. In 2021 after seawater intrusion, microbial gene abundance associated with denitrification increased, while that of DNRA did not change significantly. These changes in gene abundance align mostly with alterations in nitrogen transformation rates. In summary, ecological change effects in N cycling after the dam opening (N retention or release, that is, eutrophication deterioration or mitigation) depend on the degree of seawater intrusion and the underlying freshwater conditions, which constitute the extent of seawater-trapping.